Carbon Electrodes from Corn Stalk Core for Supercapacitor Application - Juliani, Rita (Journal of Technomaterial Physics, 2019)
The natural pore structure of corn stalk core potentially contributes as a basic material for activated carbon. The activated carbon from a combination of chemical and physical activation is presented for capacitive energy storage. The chemical activation was carried out using 0.4 M KOH followed by pyrolysis process up to 600°C in an N2 atmosphere. The physical activation was conducted at various temperatures such as 600°C, 700°C, and 800°C with a CO2 gas flow rate of 10 mL/min. Supercapacitor cells were made from carbon electrodes of corn stalk core, 316L stainless steel as the current collector, duck eggshell as the separator, and 1 M H2SO4 as the electrolyte solution. The physical properties of carbon electrodes were characterized by identifying the density, surface morphology and chemical structure of carbon. The density value was obtained based on the mass, thickness, and diameter of the carbon electrode. The lowest density was found at the activation temperature of 700°C which has the potential to produce the best performance in supercapacitor cells. SEM was used to characterize the surface morphology. The activation temperature of 700°C showed the formation of irregular structures and provided large pores for the diffusion of electrolyte ions into the carbon matrix. The FTIR characterization was used to determine the carbon chain elements which formed double layers in supercapacitor cells. The electrochemical properties of supercapacitor cells were tested using cyclic voltammetry. Specific capacitances at the activation temperature of 600°C, 700°C, and 800°C were 90 Fg-1, 108.92 Fg-1, and 44.875 Fg-1, respectively. These results showed that the activation temperature of 700°C was the best temperature in the preparation of supercapacitor electrodes from corn stalk core as the biomass material.